2014
DOI: 10.1002/term.1915
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effects of varying frequency of mechanical stimulation in a cycle-by-cycle manner on engineered cardiac construct function

Abstract: Mechanical stimulation has been used extensively to improve the function of cardiac engineered tissue, as it mimics the physical environment in which the tissue is situated during normal development. However, previous mechanical stimulation has been carried out under a constant frequency that more closely resembles a diseased heart. The goal of this study was to create a bioreactor system that would allow us to control the mechanical stimulation of engineered cardiac tissue on a cycle-by-cycle basis. This uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…The only other study to report both TTP and RT50 in NRVM based 2 week old EHTs was the work of Morgan et al 53. Their reported RT50 and TTP values (125 and 150 ms respectively at 0.5 Hz pacing)53 are notably slower than those observed in our method. This difference could potentially be explained by our T3 media substitution54.…”
Section: Discussioncontrasting
confidence: 59%
“…The only other study to report both TTP and RT50 in NRVM based 2 week old EHTs was the work of Morgan et al 53. Their reported RT50 and TTP values (125 and 150 ms respectively at 0.5 Hz pacing)53 are notably slower than those observed in our method. This difference could potentially be explained by our T3 media substitution54.…”
Section: Discussioncontrasting
confidence: 59%
“…Isolated neonatal CMs cultured in a dynamic bio-reactor were used to evaluate variable frequency of mechanical stimulation in a cycle-by-cycle manner (see the mechanical descriptions in Fig. 4E) [313]. Gaussian stimulation may promote physiological over pathological hypertrophy as shown by lower ratios phosphorylated ERK1/2 to ERK1/2.…”
Section: Mechanical Stimulation Of Cardiac Cells and Tissuesmentioning
confidence: 99%
“…The design of the reactor control system enables the development of electrical and mechanical stimulation regimes that can mimic both healthy function (isovolumic contraction) as well as characteristic changes in disease. Control of stimulation regimes also enables the integration of construct “exercise” to replicate changes in heart rate [33,34,313,383]. …”
Section: Figmentioning
confidence: 99%
“…Morgan et al 174177 further pointed out that the combined electrical and mechanical stimulations are necessary for improved functional properties plus the timing of the combined stimulation also greatly affect the engineered cardiac tissue. Moreover, a very interesting phenomenon was observed by Morgan et al 174,175 ; they found that, when the electrical stimulus was slightly delayed after the beginning of mechanical stimulus, the yield constructs had improved function and better expression of proteins responsible for cell–cell communication and contractility.…”
Section: Bioreactors For Promoting Cell Differentiation Functionamentioning
confidence: 99%
“…Hence, one subtle mimicking of the biophysical environment during isovolumic contraction is able to improve quality of the cardiac construct, implying that bioreactor design and the conditioning regimen planning should more accurately reproduce in vivo physiological conditions. 174177 …”
Section: Bioreactors For Promoting Cell Differentiation Functionamentioning
confidence: 99%